Older adults' technology anxiety as a barrier to digital inclusion: a scoping review - Kim, Ha-Neul; Freddolino, Paul P.; Greenhow, Christine (Educational gerontology, 2023)
Existing research has found that older adults experience technology-related anxiety, resistance, fear, and even technophobia when using digital devices or systems. However, there has been limited conversation in the literature about how scholars define these terms differently, where this anxiety comes from, how current studies or practices deal with such anxiety, and what are possible solutions. To advance this conversation, this article used a scoping review methodology to synthesize themes in the literature on technology resistance among older adults. The scope of the literature review was limited to articles published in peer-reviewed journals. The search keywords included: older adults, seniors, elderly, older people, older population, technology anxiety, resistance to technology, technophobia, digital anxiety, digital resistance, computer anxiety, and resistance to computer. Using PRISMA standards for scoping reviews, 24 articles were selected and analyzed. This review revealed that different terms were used to conceive of and indicate the responses of older adults in showing anxiety, feeling nervous, and hesitating to use technology. A synthesis of studies revealed that research has been done with associated variables such as technology use, perceptions, and intentions, but more research is needed to examine the predictors of discomfort with technology in order to identify effective approaches to resolving technology-related anxiety and hesitancy among older adults. This review contributes to the current understanding of technology anxiety among older adults by illuminating conceptions of the digital divide as it pertains to older populations and suggesting avenues to overcoming it.